Enhanced Recovery After Surgery Protocol in Emergency Laparotomy: A Randomized Control Study - Sharma, Jyoti; Kumar, Navin; Huda, Farhanul; Payal, Yashwant Singh (The Surgery Journal, 2021)
Introduction There is established evidence on the role of enhanced recovery after surgery (ERAS) protocols in elective surgeries but its effectiveness in emergency surgeries has been nominally studied. We aimed at studying the feasibility and effectiveness of ERAS protocols in patients undergoing emergency abdominal surgery for intestinal perforation and small bowel obstruction and compare their surgical outcomes with conventional care.Materials and methods This prospective randomized study was performed for a period of 16 months. A total of 100 patients presenting either with intestinal perforation or acute small bowel obstruction were recruited; 50 each in the ERAS and the conventional care groups. The primary outcomes studied were the postoperative length of stay and 30-day morbidity and mortality.Results It was seen that the median (interquartile range) of the duration of hospital stay in the ERAS group was 4 (1) days while it was 7 (3) days in the conventional care group, which was statistically significant (W = 323.000, p ≤ 0.001). Similarly, postoperative morbidities like a chest infection and surgical site infections) were significant in the conventional care group.Conclusion The ERAS protocols are safe and effective in emergency surgeries and result in a better postoperative outcome.
Keywords: emergency gastrointestinal surgery; enhanced recovery after surgery protocol; emergency laparotomy